Chemical composition and fatty acid profile of rhea (Rhea americana) meat - Romanelli, Pedro Fernando [UNESP]; Trabuco, Elizeu; Scriboni, Andreia Borges; Visentainer, Jesui Vergilio; de Souza, Nilson Evelazio (Archivos Latinoamericanos Nutricion, 2008)
The purpose of this work was to determine the proximate composition and fatty acid profiles of the Gastrocnemius pars interna intramuscular fat (IMF) of rhea (Rhea americana) thighs. The birds were bred in captivity, fed with balanced feed (Nutriavestruz Crescimento - Purina) and kept in a pen with grass ad lib. The birds of both sexes used in the research weighed 23 kg on average and were aged about twelve (12) months old. They were subjected to hydric diet (12 h) before slaughtering by electric shock. The rhea meat showed an average moisture, protein, ash and total lipid contents of 74.1%, 22.8%, 1.5% and 1.6%, respectively. It was noticed the predominance of monounsaturated fatty acids (MUFA) in intramuscular fat (IMF), 42.3% and a high percentage of polyunsaturated fatty acids (PUFA), 29.7%.. The fatty acids found in higher proportion in rhea IMF were: 18:2n-6 (24.33%), 18: 1n-9 (19.25%),16:0 (13.70%),22: 1n9 (11.40%),18:0 (10.66%),15: 1n-10 (8.62%),24: 1n-9 (2.90%) and 20:4n-6 (1.72%). The PUFA/SFA and n-6/n-3 ratios were 1.06 and 31.30, respectively. The consumption of rhea meat is a healthy alternative to red meat as it points to a lower susceptibility to cardiovascular diseases caused by the high consumption of fat comparatively to the consumption of meat from most domesticated animals.

El objetivo de este trabajo fue determinar la composición aproximada y el perfil de ácidos grasos en la carne de la parte intramuscular IMF) interna de la pierna de ñandú (Rhea americana). Las aves fueron criadas en cautiverio, alimentadas con ración balanceada (Nutriavestruz Crescimento – Purina) y mantenidas en corral con pasto ad lib. La edad media de las aves de los dos sexos usados en la investigación fue de 12 meses y el peso medio de 23 kg. Fueron sometidas a dieta hídrica por 12 horas antes de matarlas por aplicación de descarga eléctrica. Los resultados de contenido medio de humedad, proteína, cenizas y lípidos totales fue de 74.1%, 22.8%, 1.5% y 1.6%, respectivamente. Fue posible notar una predominancia de ácidos grasos monoinsaturados (MUFA) en la gordura intramuscular (IMF) ), 42.3% y un alto porcentaje de ácidos grasos poli-insaturados (PUFA), 29.7%. Los ácidos grasos encontrados en mayor proporción en rhea IMF fueron: 18:2n 6 (24.33%), 18:1n 9 (19.25%), 16:0 (13.70%), 22:1n9 (11.40%), 18:0 (10.66%), 15:1n 10 (8.62%), 24:1n 9 (2.90%) y 20:4n 6 (1.72%). La PUFA/SFA (ácidos grasos saturados) y relación n-6/ n-3 fue 1.06 y 31.30, respectivamente. El consumo de carne de ñandú es una alternativa saludable frente a la carne roja pues su consumo presenta una menor susceptibilidad a enfermedades cardiovasculares causadas por alto consumo de grasas cuando comparado con el consumo de carne de animales domesticados.
Composición química y perfil de ácidos grasos de la carne de ñandú (Rhea americana)
Keywords: ratite; Rhea americana; fatty acid profile; rhea; Aves corredoras; Rhea americana; Ácidos grasos; ñandú